The business model of a university research lab - Chesbrough, Henry William; Abrams, Zeev R. (London : SAGE Publications Ltd, 2017)
This case study teaches students how to think through the management of open innovation in the context of a different setting such as a university research laboratory. The goal of the case is to show students that there are significant management issues in the organization and selection of models for academic research. Open innovation, in turn, may require students to bend and flex the model in different contexts or situations. In the process of analyzing this case, students must take into consideration the context of the organization, the culture, and the drivers and metrics for success.
Originally published in Chesbrough, H., & Abrams, Z. R. (2011). The business model of a university research lab. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Management -- Case studies; Research -- Management -- Case studies